2022
DOI: 10.1016/j.ajoc.2022.101281
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral acute macular neuroretinopathy in a young woman after the first dose of Oxford–AstraZeneca COVID-19 vaccine

Abstract: Purpose To report a case of bilateral acute macular neuroretinopathy following the first dose of Oxford-AstraZeneca COVID-19 (coronavirus disease 2019) vaccine in a young, Caucasian, and healthy woman. Observations A 25-year-old Caucasian female patient presented to the ophthalmology department of Dijon University Hospital with a 3-week history of black spots and paracentral scotoma in both eyes. She had no past medical history and was using the combined estrogen-proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Furthermore, several case reports were published linking AMN to vaccination against the SARS-CoV-2 virus. In all reports, symptoms occurred in the immediate post-vaccination period of 1-3 days[16][17][18][19][20]. In the latter, no direct viral insult is plausible to cause the AMN.Consistent with current understanding of the risk factors for AMN, the three cases described in our case series experienced a concurrent viral upper respiratory infection, all of them consisting of COVID-19.…”
supporting
confidence: 77%
“…Furthermore, several case reports were published linking AMN to vaccination against the SARS-CoV-2 virus. In all reports, symptoms occurred in the immediate post-vaccination period of 1-3 days[16][17][18][19][20]. In the latter, no direct viral insult is plausible to cause the AMN.Consistent with current understanding of the risk factors for AMN, the three cases described in our case series experienced a concurrent viral upper respiratory infection, all of them consisting of COVID-19.…”
supporting
confidence: 77%
“…In addition, several cases of AMN and paracentral acute middle maculopathy were reported, which were presumed to be caused by subclinical retinal microvascular vasculitis affecting deep capillary layer and choroidal layer after the first dose of inactivated SARS-CoV-2 vaccine. [ 5 , 24 , 25 ] These abovementioned data regarding to microvascular events and thrombosis after COVID-19 vaccination seem to highlight the importance of screening for retinal vascular involvement in healthy subjects.…”
Section: Discussionmentioning
confidence: 96%
“… [3] The most commonly reported retinal adverse events were acute macular neuroretinopathy (AMN) and paracentral acute middle maculopathy (PAMM) [4] . Although the pathogenesis of AMN remains uncertain, a retinal microvascular etiology affecting the deep retinal capillary plexus (DCP) was proposed as the possible mechanism [5] . Furthermore, several recent studies reported on ocular vascular events, such as central and branch retinal vein and retinal arterial occlusion, where possible hypercoagulable states following vaccination could be suspected.…”
Section: Introductionmentioning
confidence: 99%
“… Publication Date Diagnosis Age Sex Hormonal Birth Control Use? Vaccine Onset of Symptoms After Vaccine September 1, 2021 17 AMN (bilateral) 20 Female Vaginal hormonal contraception Pfizer 2 days September 23, 2021 18 AMN (bilateral) 23 Female Oral contraception AstraZeneca 1 day November 17, 2021 19 AMN (bilateral) 21 Female No AstraZeneca 3 days January 1, 2022 20 AMN (unilateral) 22 Female No AstraZeneca 5 days January 1, 2022 21 AMN (bilateral) 26 Female Oral contraception Johnson & Johnson 2 days January 20, 2022 22 AMN (bilateral) 25 Female Oral contraception AstraZeneca 1 day January 20, 2022 23 AMN (bilateral) 31 Female Oral contraceptive AstraZeneca 2 days January 20, 2022 …”
Section: Discussionmentioning
confidence: 99%